The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/14651858.cd002928.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing partner support to improve smoking cessation

Abstract: BackgroundWhile many cessation programmes are available to assist smokers in quitting, research suggests that partner involvement may encourage long-term abstinence. ObjectivesThe purpose of this review was to determine if an intervention to enhance partner support helps smoking cessation when added as an adjunct to a smoking cessation programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…37,55 All of those interventions were delivered by professional counselors; none involved family and peer networks simultaneously as we did. Although there are two published LHW outreach smoking cessation intervention studies, one targeted Southeast Asian men including Vietnamese Americans 27 and the other targeted Latino smokers, 56 they were focused on individual smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,55 All of those interventions were delivered by professional counselors; none involved family and peer networks simultaneously as we did. Although there are two published LHW outreach smoking cessation intervention studies, one targeted Southeast Asian men including Vietnamese Americans 27 and the other targeted Latino smokers, 56 they were focused on individual smokers.…”
Section: Discussionmentioning
confidence: 99%
“…21,35,36 To our knowledge, there is no published smoking cessation intervention randomized trial that has simultaneously targeted both family and peer networks of smokers in any population within or outside of the United States. 37 LHW outreach, a social network-based intervention, has been effectively applied across different behaviors such as immunization uptake and cancer screening [38][39][40] and diabetes management. 41 A LHW shares the same ethnicity, cultural and language background of the targeted populations and who, though not a health professional, has received training to deliver specific health messages via individual or small group settings.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that these interventions were not successful in increasing social support. 14,15 For the development of effective interventions it is, however, necessary to understand the association between social support and smoking in couples by applying dyadic designs and considering both partners of a couple. 16,17 To date, research on social support has mostly focused on individuals, but in daily life most individuals are embedded in close dyadic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that buddy-behaviours might be somewhat intractable and that motivational-buddies may quickly return to their default (motivational) style when no longer under the influence and guidance of researchers or programme providers (see Carlson, Goodey, Bennett, Taenzer, & Koopmans, 2002;Glasgow, Klesges, & O'Neill, 1986;Park, Tudiver, & Campbell, 2012 for more detailed perspectives). The relative merits of training buddies versus selecting naturally-supportive buddies needs to be rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%